2000
DOI: 10.1348/014466500163185
|View full text |Cite
|
Sign up to set email alerts
|

Carers' attributions for challenging behaviour

Abstract: The results are discussed in relation to the concept of helping and the experience of carers coping with challenging behaviours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
117
6

Year Published

2003
2003
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(132 citation statements)
references
References 20 publications
9
117
6
Order By: Relevance
“…Jones & Hastings (2003) suggested that this may have been because staff responses to challenging behaviour may vary depending on topography. Stanley & Standen (2000) also demonstrated that the more externalising forms of challenging behaviour (e.g. destructive behaviour) are associated with increased staff attributions of client control, negative staff affect and reduced propensity to help, while self-directed challenging behaviour (e.g.…”
Section: Care Staff Attributions Toward Self Injurious Behaviour Exhimentioning
confidence: 96%
“…Jones & Hastings (2003) suggested that this may have been because staff responses to challenging behaviour may vary depending on topography. Stanley & Standen (2000) also demonstrated that the more externalising forms of challenging behaviour (e.g. destructive behaviour) are associated with increased staff attributions of client control, negative staff affect and reduced propensity to help, while self-directed challenging behaviour (e.g.…”
Section: Care Staff Attributions Toward Self Injurious Behaviour Exhimentioning
confidence: 96%
“…Stanley and Standen [17] examined how carers of people with brain injuries explained challenging behaviours such as violent outbursts. The more independent the person with the injury was in their daily activities, the more likely the carer was to attribute the behaviour to being within the person's control and to feel negatively towards the person.…”
Section: Attributions About People With Brain Injuriesmentioning
confidence: 99%
“…At worst this means that staff can intervene in ways that are unhelpful and unsupportive (Stanley & Standen, 2000). Our attributions i.e.…”
Section: Introductionmentioning
confidence: 91%